Biopower, Discipline, and Resistance in The Hunger Games (2012): A Foucauldian Analysis - Lee, Georgia Love; Silaen, Gwyneth Lillian; Saputra, Felicia Celine; Jacobus, Benaiya Tristan; Noah, Abimanyu; Hutagalung, Rachell Anastasya (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study examines The Hunger Games (2012), directed by Gary Ross, through Michel Foucault’s concepts of power, discipline, and biopolitics. Using qualitative content analysis, the research investigates how the Capitol maintains dominance over the districts and how resistance emerges within oppressive systems. The findings reveal: 1) the Capitol’s exercise of biopower reduces life to political control, exemplified in the ritual of the Reaping where sacrifice is normalized as governance. 2) disciplinary power is reinforced through spectacle and propaganda, such as televised ceremonies and the constant reminder of rebellion, which embed fear and institutionalize trauma across generations. 3) despite these mechanisms of control, acts of resistance emerge: Katniss Everdeen and Peeta Mellark subvert Capitol authority through personal defiance, illustrating Foucault’s view that power inevitably produces resistance. By highlighting these dynamics, the film underscores how power operates not only through coercion but also through cultural production, surveillance, and ideology. This analysis contributes to the understanding of how popular culture reflects and critiques structures of domination and the possibilities of resistance in both fictional and real-world contexts.